Hierarchy and inequality in research: Practices, ethics and experiences. (October 2022) - Frers, Lars; Meier, Lars
Research as a social practice enacts social hierarchies in the relation between researcher and the researched. Taking up the critique of the consequences of such hierarchies in the production of knowledge, participatory methods aim to decolonize this power relation. This article contributes to this topic by discussing limits of participation, highlighting the often unexpected reemergence of power and hierarchies in a leveled research field. We take a closer look at how inequalities are emerging and negotiated in the research process. Troublings of hierarchies during the research process are considered as eminently productive for the analysis of social inequalities and for maintaining a precarious ethics of care in the research process. Other articles that also contribute to the special issue opened by this contribution analyze sources and expressions of hierarchy and power troubles during qualitative research by putting a specific focus on unforeseen challenges, inversions, and obstacles that arise during research processes. The contributions demonstrate what specific insights into social inequalities can be gained through an analytical focus on such troubles. It is demonstrated that a critical reflection of inequalities in research relations can also be a contribution to research on social inequalities in general.